2009
DOI: 10.1017/s002081830909002x
|View full text |Cite
|
Sign up to set email alerts
|

The Discursive Process of Legalization: Charting Islands of Persuasion in the ICC Case

Abstract: For many political observers the successful creation of the International Criminal Court (ICC) came as a surprise, as major powers, in particular the United States, had opposed the plans for the ICC. Moreover, the institutional design of the ICC entails enormous sovereignty costs for states but only uncertain benefits. An analysis of the negotiations suggests that the court's successful creation can be attributed to persuasion and discourse within negotiations, that is, a shift in states' interests. The articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
123
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(133 citation statements)
references
References 39 publications
3
123
0
7
Order By: Relevance
“…The American story is particularly interesting as the United States has never ratified the Rome Statute and generally keeps a critical distance from the ICC. William Schabas (2004) in fact writes about "United States hostility to the International Criminal Court" (see also Deitelhoff 2009). Specifically with regard to Darfur, the United States initially displayed considerable resistance against a referral of the Darfur situation to the ICC.…”
Section: Discussionmentioning
confidence: 99%
“…The American story is particularly interesting as the United States has never ratified the Rome Statute and generally keeps a critical distance from the ICC. William Schabas (2004) in fact writes about "United States hostility to the International Criminal Court" (see also Deitelhoff 2009). Specifically with regard to Darfur, the United States initially displayed considerable resistance against a referral of the Darfur situation to the ICC.…”
Section: Discussionmentioning
confidence: 99%
“…Business organisations gain power from liaising with political elites "as business is the key motor of economic growth on which the political system is so dependent". In other cases, NGOs have successfully used strategies of persuasion to affect changes the positions of states' interests (Deitelhoff, 2009). Kolk (2001) found that business organisations generally favour voluntary initiatives and self-regulation to public regulation, partly because self-regulation enables the self-regulator to decide for themselves what they want to do.…”
Section: Negotiating and Protecting Interests In Intergovernmental Prmentioning
confidence: 99%
“…Other studies -probably more interesting to political scientists -include the analysis of the emergence of cosmopolitanism and cosmopolitan norms (Benhabib, 2006;Delanty, 2013); cases of normative learning in legal revolutions (Brunkhorst, 2014); the creation of the International Criminal Court (Deitelhoff, 2009); environmental discourse and environmental policy making (Eder, 1995); informal political talk and learning processes regarding the definition of social identities and the formation of political perspectives (Walsh, 2004); Germany's path into modernity and the evolution of the German political culture during the 18 th and 19 th centuries (Eder, 1991), or the democratising dynamics of the European public sphere (Eder, 2007b;Statham and Trenz, 2014;Trenz and Eder, 2004). These are mostly case studies in which the goal is to account for the unfolding of events in time, examining turning points and how previous events paved the way for subsequent ones, whilst foreclosing alternative courses of action.…”
mentioning
confidence: 99%
“…First, it has been contended that discourse might give rise to "islands of persuasion" (Deitelhoff, 2009), this is, it might shape communicative interactions in such a way that they closely approximate the ideal speech situation. This is what the standard, political theory perspective would also call deliberation.…”
mentioning
confidence: 99%
See 1 more Smart Citation